SISTEM INFORMASI RE-PENDAYAGUNAAN PERANGKAT DESA PURNA TUGAS DENGAN METODE KEY PERFORMANCE INDICATOR (KPI) - sri; Fajar Nugraha, S.Kom., M.Kom; Noor Latifah, S.Kom., M.Kom (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Village government plays a crucial role in public services, necessitating effective human resource management, including the empowerment of retired village officials. However, the ongoing process in Mijen District, Demak Regency, is still manual, resulting in inefficiency, unintegration, and a tendency towards subjectivity. This study aims to develop a web-based Re-Employment Information System for Retired Village Officials by implementing the Key Performance Indicator (KPI) method as a measuring tool for performance assessment and reassignment eligibility. Data collection methods were conducted through observation, interviews, and literature studies while system development uses the Software Development Life Cycle (SDLC) with the Waterfall model. The KPI indicators used include attendance, job responsibility, understanding of village legal products, information technology capabilities, length of service, integrity, and social involvement. The research results are a web-based information system capable of managing village official data, conducting structured performance assessments, and generating objective reassignment recommendations based on KPI values. This system is also equipped with data management features, evaluation processes, and presentation of assessment results reports. With this system, it is hoped that it can increase efficiency, transparency, and objectivity in the process of empowering retired village officials and assist village and sub-district governments in making more precise and measurable decisions.